Attitude towards plagiarism among Iranian medical students - Ghajarzadeh, Mahsa (Journal of medical ethics, 2013)
In recent years, scientific misconduct has received significant attention within the scientific community. Plagiarism is the most frequent type of scientific misconduct and is defined as ‘unauthorised appropriation of another's work, ideas, methods, results or words without acknowledging the source and original author’.1 ,2 …